2018
DOI: 10.1002/ldr.3162
|View full text |Cite
|
Sign up to set email alerts
|

Natural regeneration on land degraded by coal mining in a tropical climate: Lessons for ecological restoration from Indonesia

Abstract: There are few examples of primary succession from tropical conditions, especially on land degraded by human activity, for example, mine wastes. Such studies would assist in informing ecological restoration of these degraded sites. Here, a chronosequence approach was used to investigate early-stage primary succession on overburden spoil wastes derived from coal mining in a tropical climate over a 64-month period. Plant species composition and several microclimatic and spoil physicochemical and microbial propert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 40 publications
1
25
0
1
Order By: Relevance
“…In this study, there were 6, 10, 9, and 13 modules in the eigengene analysis of the PB, ZC, YQ, and DT networks, respectively. The module eigengenes explained 53%-81%, 61%-77%, 53%-81%, and 52%-70% of the variations in relative species abundance across the different samples in the PB, ZC, YQ, and DT networks, respectively ( Figure S1-S4 in Additional file [5][6][7][8]. All of the eigengenes explicated over 50% of the observed variations, which revealed that these eigengenes could represent species shift across different samples in the individual modules.…”
Section: Eigengene Network Analysismentioning
confidence: 91%
See 1 more Smart Citation
“…In this study, there were 6, 10, 9, and 13 modules in the eigengene analysis of the PB, ZC, YQ, and DT networks, respectively. The module eigengenes explained 53%-81%, 61%-77%, 53%-81%, and 52%-70% of the variations in relative species abundance across the different samples in the PB, ZC, YQ, and DT networks, respectively ( Figure S1-S4 in Additional file [5][6][7][8]. All of the eigengenes explicated over 50% of the observed variations, which revealed that these eigengenes could represent species shift across different samples in the individual modules.…”
Section: Eigengene Network Analysismentioning
confidence: 91%
“…Assessment of the diversity and activity of the soil microbial community is essential to evaluate the success of reclamation or restoration. However, few studies have been conducted on the soil microbial community diversity where there is a high groundwater level, or in semiarid damaged mining areas [5][6][7]. In this study, we identified the dominant bacteria, which was critical to enhance our understanding, and determined the ecological attributes of soil bacterial communities, which are abundant and ubiquitous in the soil at different mining areas.…”
Section: Introductionmentioning
confidence: 99%
“…Overall, the effects of open-pit mining on biodiversity and habitat quality are lasting. As similar studies report [30,56], open-pit mining has many serious consequences for ecosystems, including surface soil stripping, habitat degradation, and landscape fragmentation. The excavation, human occupation, and wastes disposal associated with mines reduces and fragments healthy landscape patches, decreasing connectivity, and leading to habitat islands of diminished size.…”
Section: Analyzation Of Results For Recognition Of Ecological Landscamentioning
confidence: 81%
“…Soil microorganisms are an essential part of the soil ecosystem. SMCs play a key role in the processes of decomposing soil organic matter, nutrient cycling and utilization of nutrients by plants (Novianti et al, 2018;Yuan et al, 2018). After land reclamation, changes in the soil physical and chemical properties may provoke changes in key soil attributes (e.g.…”
Section: Introductionmentioning
confidence: 99%